Correlates of climate change skepticism - Leka, Jona; Furnham, Adrian (Frontiers in Psychology, 2024)
While much research has examined the correlates of climate change beliefs from an alarmist perspective, less work has systematically measured climate change skepticism. This study aims to create a comprehensive tool capturing climate skeptics’ beliefs and test its association with individual difference variables. 502 European adults completed a 22-item questionnaire on climate change (CC) skepticism as well as measures of ambiguity tolerance, belief in a just world (BJW), dark-side personality traits, and self-esteem. Principal components analysis revealed a four dimension structure of CC. Political ideology was the most consistent and significant predictor across the climate change skepticism factors. Dark-side traits, also played a role. Future research should further validate this measure and explore how climate change information could be tailored to different audiences. Understanding the nuances and causes of climate skepticism can enable more effective communication to promote sustainability.